DNA hypermethylation of the promoter attenuates forkhead box protein 3 (FOXP3) expression in hepatocellular carcinoma cells - Lin, Zewei; Liu, Xu; Liu, Xiaoping; Liu, Jikui (Translational Cancer Research, 2019)
Background: Forkhead box protein 3 (FOXP3) plays a pivotal role in tumor progression and impacts the methylation status and levels of expression of an associated promoter region. However, the methylation status and how this parameter impacts the FOXP3 promoter in cases of human hepatocellular carcinoma (HCC) remains unclear. This study sought to investigate the relationship between methylation status of transcriptional FOXP3 gene promoter and the levels of expression of FOXP3 in human HCC afflicted cell lines and tissues. Methods: We used quantitative real-time PCR (Real-time qPCR) to detect the levels of expression of FOXP3 mRNA in human HCC afflicted cell lines and tissues. Immunohistochemistry and western blot were used to examine protein expression levels of FOXP3 in human HCC afflicted cell lines and tissues. Reverse transcription PCR was used to detect the levels of expression of the FOXP3 gene promoter in HCC afflicted cell lines. Finally, methylation sequencing was used to examine the influences of epigenetic regulation upon the FOXP3 promoter region in HCC afflicted cell lines. Results: Levels of FOXP3 expression were down-regulated in HCC afflicted tissues compared with adjacent non-tumorous tissues. Levels of expression of FOXP3 in portal vein tumor thrombus (PVTT) were much lower than were levels in HCC afflicted tissues. Further, FOXP3 was abnormally expressed in HCC afflicted cell lines. The FOXP3 promoter was also abnormally expressed among HCC afflicted cell lines. Lastly, the FOXP3 promoter was hypermethylated in HCC afflicted cell lines. Conclusions: Results suggest that levels of expression of the FOXP3 promoter were decreased for measures of both mRNA and protein expression levels in HCC afflicted tissues and cell lines. The FOXP3 gene promoter region when hypermethylated may help inhibit FOXP3 expression and the development and progression of HCC.